2022
DOI: 10.3390/app12126187
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Components of CNC Lathe Based on Dynamic Influence of Fault Propagation

Abstract: Identifying the key components of CNC lathe and analyzing the fault propagation behavior is a powerful guarantee for the fault diagnosis and health maintenance of CNC lathe. The traditional key component identification studies are mostly based on the feature parameter evaluation of the fault propagation model, disregarding the dynamics and influence of fault propagation. Therefore, this paper proposes a key component identification method based on the dynamic influence of fault propagation. Based on the CNC la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The different locations of machining center components cause the influences of propagation to be different. According to the principle of third-order influence [29], faults in machining center components will not only propagate to the adjacent components, but they may also have an impact on the components within the third order. Therefore, the fault propagation probability and the fault propagation risk are introduced into the improved ASP algorithm.…”
Section: Evaluation Of Fault Propagation Indexes Based On the Improve...mentioning
confidence: 99%
“…The different locations of machining center components cause the influences of propagation to be different. According to the principle of third-order influence [29], faults in machining center components will not only propagate to the adjacent components, but they may also have an impact on the components within the third order. Therefore, the fault propagation probability and the fault propagation risk are introduced into the improved ASP algorithm.…”
Section: Evaluation Of Fault Propagation Indexes Based On the Improve...mentioning
confidence: 99%
“…In response to this issue, many scholars have conducted research from the perspective of the whole machine, with the goal of identifying key components. For example, Luan et al 12 have constructed a dynamic identification method for key components from the perspective of mechanical system dynamics. Case studies have shown that this method is superior to traditional fault intensity-based identification methods.…”
Section: Introductionmentioning
confidence: 99%